BILINGUAL PORTFOLIO-BASED WRITING INSTRUCTION IN IMPROVING STUDENTS’ WRITING PERFORMANCE - Domingo, Joyledesma (International Journal of Arts, Sciences and Education, 2022)
Abstract The primary focus of this study was to determine the effect of bilingual portfolio-based writing instruction to Senior High School students’ skill in writing. HUMSS students involved in this study were enrolled in work immersion subject. A quasi-experimental research particularly pretest-posttest design was adopted of which technique was gleaned from Nezakatgoo (2011). The pre-test was applied to both the treatment group and control group to prove homogeneity of writing performance. Later in the study, a post-test was implemented for both groups who received writing instruction from the same teacher. The treatment group was exposed to bilingual portfolio-based writing instruction while the control group was exposed to traditional writing instruction (non-portfolio). Data were analyzed using frequency, percentage, standard deviation, Paired Sample T-test and Cohen’s D. Results showed that students exposed to bilingual portfolio writing instruction had better writing performance compared to those students who received traditional writing instruction. There was a significant difference on the pretest and posttest scores of the treatment group while there was no significant difference in the test scores of control group. The findings of the study highlighted that bilingual portfolio-based instruction enhances writing skill of secondary students. Likewise, when language learners are provided with appropriate writing instruction founded on familiar language, their writing performance in English is likely developed.